Differences in knowledge of oral health before and after counseling between lecture and role play method - Sari, Rini Yufita; Chemiawan, Eka; Sudarsana, Nandang (Padjadjaran Journal of Dentistry, 2010)
Introduction: Oral health education is one way to increase understanding in maintaining oral health. This will be effective if started at an early age. The purpose of this study is to analyzed differences in knowledge before and after counseling between lectures and play methods. Methods: Quasi experimental methods are used in this study. Samples were selected through purposive sampling, 27 sixth grade students and 12 elementary school students from Cikawao village were taken as sample. Questionnaires before and after counseling are used to address the differences in the knowledge of each student. Group 1 was given counseling on oral health through the lecture method while group 2 through the play method. Results: The study found that the increase in the mean score of the play method (6.53) was higher than the lecture method (4.75). The difference in knowledge after counseling between the lecture and play methods was significant among elementary school students. Conclusion: There are differences in oral health knowledge before and after counseling between the lecture method and the play method. The knowledge obtain after counseling with play methods is better when compared to lecture method.